Looking for boundary spanners: an exploratory study of critical experiences of coaches in sport-for-development programmes. Issue 4 (4th May 2022) - Van der Veken, Karen; Harris, Kevin; Delheye, Pascal; Lauwerier, Emelien; Willems, Sara
ABSTRACT: Given that sport-for-development (SfD) requires the intentional use of sport as a tool to realize developmental goals in complex contexts, there is a need for reflexive SfD coaches who can successfully contribute to the delivery of programmes. In this study, we explore the lived experiences of SfD coaches in a selection of programmes in Flanders, Belgium. We look at their responsibilities, perceived competencies and the conditions that need to be in place in order to realize SfD goals. Qualitative data spanning a four-year research project were analysed in order to understand how, why and in what contexts coaches contribute to SfD programmes. The analysis unearthed a boundary-spanning coach profile, establishing emotional connectivity, working in a transprofessional manner, and occupying professional hybridity that adapts to context continuously. These results provide an important contribution for SfD practice and policy, nourishing reflection on the 'ideal' SfD coach profile, and how it could be generated within the most complex times.